Chaperone-like Activity and Quaternary Structure Dynamics of HSPB5 in Crowded Milieu - Natalia A. Chebotareva; Svetlana G. Roman; Vera A. Borzova; Tatiana B. Eronina; Valeriya V. Mikhaylova; Boris I. Kurganov (Current Advances in Chemistry and Biochemistry Vol. 7, 2021)
Small heat-shock proteins (sHSPs) are ATP-independent molecular chaperones that interact with partially unfolded proteins, preventing their aberrant aggregation, thereby exhibiting a chaperone-like activity. Dynamics of the quaternary structure plays an important role in the chaperone-like activity of sHSPs. However, relationship between the dynamic structure of sHSPs and their chaperone-like activity remains insufficiently characterized. Many factors (temperature, ions, a target protein, crowding etc.) affect the structure and activity of sHSPs. The least studied is an effect of crowding on sHSPs activity. In this work the chaperone-like activity of HSPB5 was quantitatively characterized by dynamic light scattering using two test systems, namely test systems based on heat-induced aggregation of muscle glycogen phosphorylase b (Phb) at 48°C and dithiothreitol-induced aggregation of a-lactalbumin at 37°C. Analytical ultracentrifugation was used to control the oligomeric state of HSPB5 and target proteins. The possible anti-aggregation functioning of suboligomeric forms of HSPB5 is discussed. The effect of crowding on HSPB5 anti-aggregation activity was characterized using Phb as a target protein. The duration of the nucleation stage was shown to decrease with simultaneous increase in the relative rate of aggregation of Phb in the presence of HSPB5 under crowded conditions. Crowding may subtly modulate sHSPs activity. In addition, biopolymers (proteins) capable of reversibly changing the state of association/dissociation or accepting an expanded or compact state of the quaternary structure can change the level of excluded volume in cells.